Factors of Halal Awareness in Cosmetic Products Among Milenial Muslimah in Indonesia - Hendy Tannady; Meilisa Alvita (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the factors that shape awareness of halal cosmetic products among millennial Muslim women in Indonesia. The data source for this study came from a sample of 100 respondents, namely millennial Muslim women who already have an income and have used halal cosmetics, which were determined using a representative purposive sampling method. Data were analyzed using factor analysis which consisted of 4 factors, namely: (1) Halal Information, (2) Availability, (3) Halal in Media, and (4) Halal Program with a total of 23 variables. The results showed that there were 6 new factors that were formed from 21 variables analyzed and contributed 68.081%, which consisted of: (1) Media Information of 31.448% had an eigen value of 6.604, (2) Halal Accessibility of 10.624% had an eigen value of 2.231 , (3) Halal Label Information of 7.928% has an eigen value of 1.665, (4) Knowledge of Halal of 7.243% has an eigen value of 1.521, (5) Halal Program of 5.784% has an eigen value of 1.215, and (6) Halal Assurance of 5.054 % has an eigenvalue of 1.061. So from these results, it is advisable for cosmetic companies to prioritize the power of halal cosmetics and disseminate knowledge about the benefits of halal cosmetic ingredients directly to millennial Muslim women. In this way it is hoped that it can increase halal awareness among millennial Muslim women